Pengaruh Knowledge Sharing dan Employee Enggement Terhadap Kinerja Karyawan Pada Perusahaan PDAM Kota Palopo - Riskawati Riskawati; Made Diah Ratna Dewi; Ni Luh Saras Santi; Raba Natahanie; Budiarti Putri Uleng (Movere Journal, 2025)
This research aims to determine (1) the influence of knowledge sharing andemployee engagement, (2) the influence of knowledge sharing on employee performance,(3) and the influence of employee engagement on employee performance at PDAM KotaPalopo. The population in this study is all employees at PDAM Kota Palopo, with a samplesize of 30 according to Roscoe's statement. The data analysis techniques used aredescriptive analysis, validity and reliability tests, and multiple linear regression analysis.The results of the study indicate that (1) knowledge sharing and employee engagementsimultaneously have a significant effect on the performance of PDAM Kota Palopoemployees, meaning that the first hypothesis in this study is accepted. This is proventhrough the F-test results with a significance value of 0.000 < 0.05. (2) Knowledge sharingpartially has a significant effect on the performance of PDAM Kota Palopo employees,meaning that the second hypothesis in this study is accepted. This was proven through thet-test results with a probability value of 0.000 < 0.05. (3) Employee engagement alsopartially significantly influences the performance of PDAM Kota Palopo employees,meaning that the third hypothesis in this study is accepted. This was proven through the ttest results with a probability value of 0.032 < 0.05.